The significance of colors and ornamentation in the CTID office in UP Diliman a descriptive study - Reyes, Joseph William S. (UP College of Home Economics, 2011)
The focus of this thesis is the office of the Clothing, Textiles and Interior Design Department of the College of Home Economics in the University of the Philippines in Diliman, Quezon City. Purposive sampling was used for this study and the thesis explored the significance of the selected office space's color scheme and ornamentation in enhancing the efficiency of the workplace. Empirical observation and phot documentation of the space were done to record its physical setting. Interviews with selected users of the space were also conducted to gather necessary information with emphasis on the following: 1.) spatial utilization, 2.) reason/s behind the design of the office and 3.) influence of the selected color scheme and decorative accessories on the users' performance at work. The findings revealed that the design of the office does not reflect the personal design preferences of the majority of the interviewed users. The color scheme used in the office was found to be chosen so that it incorporates some existing elements in the room while most of the accessories/ornaments were selected to complement the color scheme. Nevertheless, all of the interviewed users shared the same positive reception towards the space. The users also expressed that their individual performances at work were positively influenced by their work environment. The researcher concluded that the users' positive attitude towards the office space is caused by: 1.) the inherent qualities and semantic values of the colors used in the room and 2.) the ability of the users to establish sense of place through workspace personalization.